Altitudinal patterns in two syntopic species of sturnira (Mammalia: Chiroptera: Phyllostomidae) in the Montane rain forests of Argentina - Sanchez, Mariano Sebastian (2014)
We evaluated altitudinal segregation in two Sturnira species as a mechanism allowing their coexistence. Tests were devised to discern between interspecific interactions and regional responses to geographic and environmental variables, using extensive capture data from 18 montane rain forest sites. No significant correlation between captures was found. Additionally and according to the hypothesis of historical occupation of highland versus lowland forests, each species has shown specificity in their response to the geographical and environmental variables. Our results indicated that abundance patterns in these bats likely result from the regional distribution of each species rather than local interactions between them, a pattern that may have ancient roots within the group.